Serendipity : an ecologist's quest to understand nature - Estes, J. A. (James A.), 1945- (Oakland, California : University of California Press, 2016)
"To newly minted biologist James Estes, the sea otters he was studying in the leafy kelp forests off the coast of Alaska appeared to have an unbalanced relationship with their larger environment. Gorging themselves on the sea urchins that grazed among the kelp, these small charismatic mammals seemed to give little back in return. But as Estes dug deeper, he unearthed a far more complex relationship between the otter and its underwater environment, discovering that otters played a critical role in driving positive ecosystem dynamics. While teasing out the connective threads, he began to question our assumptions about ecological relationships. These questions would ultimately inspire a lifelong quest to better understand the surprising complexity of our natural world and the unexpected ways we discover it. Serendipity tells the story of James Estes's life as a naturalist and the concepts that drive his interest in researching the ecological role of large predators. Using the relationship between sea otters, kelp, and sea urchins as a touchstone, Estes retraces his investigations of numerous other species, ecosystems, and ecological processes in an attempt to discover why ecologists can learn so many details about the systems within which they work and yet understand so little about the broader processes that influence those systems. Part memoir, part natural history, and deeply inquisitive, Serendipity will entertain and inform readers as it raises thoughtful questions about our relationship with the natural world."--Provided by publisher.
In the beginning -- Understanding nature -- The Aleutian archipelago -- Sea otters and kelp forests -- A toe in the arctic ocean -- Return to Attu -- Generality and variation -- A serpentine food web -- Sea otters and the red queen hypothesis: plant/herbivore coevolution -- Sea otters and killer whales -- Megafaunal collapse -- Whale wars -- Foxes and seabirds -- A global perspective -- Retrospection -- Looking to the future.
Includes bibliographical references and index.
Keywords: Sea otter -- Ecology -- Alaska; Marine ecology; Sea otter -- Ecology; Alaska; Electronic books; Electronic book